2000
DOI: 10.1046/j.1365-2648.2000.t01-1-01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping after heart transplantation: a descriptive study of heart transplant recipients’ methods of coping

Abstract: The purpose of the study reported in this paper was to explore the coping strategies of heart transplant recipients. Using a qualitative research approach, interviews were conducted with 42 participants (35 men and seven women). Analysis of the data revealed eight coping strategies: acceptance/optimism, denial/avoidance, setting targets, comparing oneself with others, making attributions, seeking social support, having faith and changing priorities and perceptions. These are discussed in relation to the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 19 publications
(16 reference statements)
7
62
1
Order By: Relevance
“…Compared to other studies with samples including majorities of men, our findings indicate that women and men share some similar perceptions after heart transplant, 6,16 particularly acceptance and optimism, changing life goals and priorities, self-transcendence, and faith. The finding that female transplant recipients report lack of control as a perception of their illness is unique and has not been reported by investigators who included men in their samples.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Compared to other studies with samples including majorities of men, our findings indicate that women and men share some similar perceptions after heart transplant, 6,16 particularly acceptance and optimism, changing life goals and priorities, self-transcendence, and faith. The finding that female transplant recipients report lack of control as a perception of their illness is unique and has not been reported by investigators who included men in their samples.…”
Section: Discussioncontrasting
confidence: 55%
“…Participants in a similar study reported several of the coping mechanisms described by women in our sample, including optimism, acceptance, faith, and altruism. 6 Equating the application of these coping mechanisms with discovering meaning may be a logical explanation that mediates the relationship between meaning and psychological distress. Likewise, feelings of self-transcendence, self-fulfillment and the identification of changing life goals could compare with a realization of life purpose that may also directly or indirectly influence psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Τhe process of transplantation appears to have a considerable emotional impact as the recipients have to cope with a dual challenge: the loss of their own heart and the acceptance of a donor heart (Rogers, 1989;Godfrey, Maylin, & Ross-White, 2012). Kaba, Thompson and Burnard, (2000) have suggested that the need to cope with the physical loss of a heart and acceptance of a donor heart may cause agony and produce feelings of psychological distress.…”
Section: Introductionmentioning
confidence: 99%